A critical reading of oil and gas investment in the form of a production sharing contract A study in Iraqi law - Muhammad, Ayad Jawad (Journal of Legal and Political Studies, 2025)
The production sharing contract is one of the most important contracts in the field of oil and gas investment. It is a relatively new contract when compared to other oil and gas investment contracts. It is based on the principle of oil companies sharing with the state the production produced by oil fields that these investing companies sought to produce either by discovering new fields or developing existing fields. The Kurdistan Region's oil and gas investment law stipulated its adoption, while it was mentioned in the draft federal Iraqi oil and gas law . In general, the production sharing contract has a number of positive aspects, but it is not devoid of a number of negatives, although these negatives are not sufficient to eliminate this type of contract, especially if specific controls are established for resorting to it in the event of its adoption by legislation related to investment in the oil and gas sector. Keywords:- Investment, Production participation contract, Service contract, Oil licensing contracts, Concession contract, Purchase contract for the sold item
Keywords: Investment; Production participation contract; Service contract; Oil licensing contracts; Concession contract; Purchase contract for the sold item